A bone regeneration strategy via dual delivery of demineralized bone matrix powder and hypoxia-pretreated bone marrow stromal cells using an injectable self-healing hydrogel. Issue 2 (8th December 2020) - Li, Donghai; Yang, Zhouyuan; Zhao, Xin; Luo, Yue; Ou, Yi; Kang, Pengde; Tian, Meng
Abstract : Dual delivery of demineralized bone matrix (DBM) powder and hypoxia-pretreated bone marrow stromal cells (BMSCs) using an injectable self-healing hydrogel enhances bone regeneration. Abstract : Demineralized bone matrix (DBM) powder is a potential alternative bone grafting material due to its bone regeneration capacity when the supply of autogenous bone is insufficient. However, the use of DBM powder alone remains challenging in many aspects in the clinic, such as its unstable osteoinductivity due to inactivation of growth factors during the preparation process, lack of bone regeneration cells, and difficulty in handling. Herein, we report a strategy that adopts a dual delivery of DBM powder and hypoxia-pretreated bone marrow stromal cells (BMSCs) using an injectable self-healing hydrogel to enhance bone regeneration and repair a cranial bone defect in a rabbit model. The injectable self-healing hydrogel was prepared based on a double crosslinking architecture, which comprised a dynamically cross-linked Schiff-base network as a self-healing component and a borax ion cross-linked physical network that strengthened its mechanical properties. The handling of the DBM powder was improved by mixing with the hydrogel, and, more importantly, the expression of osteocalcin (OCN) and vascular endothelial growth factor (VEGF) of the encapsulated BMSCs in the hydrogel was significantly up-regulated after hypoxia-pretreatment. The in vivo study demonstrated that the use of the hydrogel alone cannot heal the cranial bone defect, while the hydrogel/BMSC composite could increase the bone formation but was inferior to the hydrogel/DBM composite. Finally, the hydrogel/DBM/BMSC composite exhibited the best bone defect repairing effects among all groups. Overall, our results demonstrate that this dual delivery approach is a promising strategy to enhance bone regeneration for bone defect repair.